MONOPHTHONGS, DIPHTHONGS AND TRIPHTHONGS IN ENGLISH: ARTICULATORY AND PHONOLOGICAL PERSPECTIVES (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article explores the categorization and characteristics of monophthongs, diphthongs, and triphthongs in English from both an articulatoryand phonological perspective. It provides a detailed examination of how these vowel sounds are produced and perceived in English speech. Monophthongs are described as pure, stable vowel sounds produced with a fixed tongue position, while diphthongs involve a glide between two vowel sounds within a syllable. Triphthongs are even more complex, comprising three vowel sounds articulated in a single syllable. The article also emphasizes the role of dialectal variation in shaping the realization of these vowel sounds, highlighting the differences in their pronunciation across accents, such as Received Pronunciation (RP) and various forms of American English. T